(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The study aims to investigate nuclear weapons - consequences for the biosphere in the case of their potential use. Understanding the devastating impact of nuclear weapons on the surrounding biological world, infrastructure, and cultural and material values poses a significant challenge for scientists. Modern theories explaining the destructive factors of nuclear weapons do not provide completely satisfactory answers and remain incomplete. This report will examine the dangers associated with the detonation of nuclear munitions, their various types, and the resulting destructive effects on our surrounding environment, as well as some of the main methods of protection.